Revitalizing Femininity: Successful Latissimus Dorsi Flap Reconstruction Following Breast Cancer Mastectomy - A Case Report - Hari, Mada Dwi; Wiramur, Affandi; Pradana, Hikam Yanwar (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
Breast cancer remains the leading cause of cancer-related deaths among women worldwide. Mastectomy, while often necessary, can profoundly impact a woman's sense of femininity and self-image. Latissimus dorsi (LD) flap reconstruction has emerged as a reliable technique for breast reconstruction following mastectomy, providing both functional and aesthetic benefits. A 44-year-old female presented with a gradually enlarging right breast lump present for two years. Physical examination revealed a 5×5×5 cm reddish mass with indistinct borders. Histopathology confirmed grade 3 infiltrating ductal carcinoma (luminal B-like, HER-2 positive). Bone survey showed multiple lytic lesions on os calvaria, suggesting metastasis. The patient was diagnosed with stage T4bN1M1 right breast cancer. Following six cycles of chemotherapy, she underwent right modified radical mastectomy with immediate LD flap reconstruction. The procedure involved designing the LD flap to match the required size, making appropriate incisions, elevating the muscle while controlling bleeding, creating a lateral tunnel for flap passage, and placing vacuum drains at both donor and recipient sites. The procedure was completed without complications. The LD flap demonstrated excellent versatility and adaptability in addressing the breast defect. Meticulous surgical planning and execution contributed significantly to the successful outcome. The procedure effectively restored breast contour and symmetry while positively influencing the patient's psychological recovery. Immediate LD flap reconstruction following mastectomy offers a reliable, safe approach that addresses both physical and psychological aspects of breast cancer treatment, ultimately revitalizing femininity and improving quality of life for mastectomy patients.